Incidence of GeoGebra software in the teaching-learning process on the derivative in the Second Year of Unified General Baccalaureate - Gallo-Calero, José Luis (2026)
This article presents a study on the use of the free software GeoGebra in the teaching and learning process of mathematics, focusing on differentiation, with the aim of demonstrating its impact on second-year students of the Unified General Baccalaureate at the "Juan Wisneth" municipal school. This is particularly relevant given that in Ecuador, the educational methodology is traditional and minimally oriented towards the digital realm. The students were divided into two groups: the first group was introduced to the program using a didactic guide, while the second group continued with the established academic curriculum provided by the institution. The research is quasi-experimental with a quantitative approach. Data was collected using three instruments: a diagnostic assessment (before the intervention), a formative assessment (during the intervention), and a summative assessment (at the end). Furthermore, this research is part of a socio-educational project with a descriptive level of detail. This finding demonstrates that the use of GeoGebra enhances student learning, as evidenced by higher scores among those who used the software. Consequently, the impact of the digital age on mathematics, particularly in the study of derivatives, encourages institutions to use free software for improved learning.